2021
DOI: 10.1051/parasite/2021008
|View full text |Cite
|
Sign up to set email alerts
|

Taeniid cestodes in a wolf pack living in a highly anthropic hilly agro-ecosystem

Abstract: The Italian wolf population in human-modified landscapes has increased greatly in the last few decades. Anthropisation increases the risk of transmission of many zoonotic infections and in this context, control of taeniid cestode species needs to be addressed from a One Health perspective. Predator-prey interactions are at the root of taeniid cestode transmission, and the wolf plays a key role in the maintenance and transmission of taeniids. To date, all available data on the taeniids of wolves in Italy refer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…Recently, Citterio et al (2021) detected T. serialis eggs in only 0.2% of 2872 red foxes collected from 2012 to 2018 in Northern Italy. Interestingly, Italian wolf ( Canis lupus italicus ), although is a deeply studied species, where hundreds of researches investigate its helminths, has never been diagnosed positive for T. serialis , also considering different regions, ecological setting (anthropic vs not anthropic), and sample size (see for example: Gori et al, 2015 ; Poglayen et al, 2017 ; Macchioni et al, 2021 ), making the red fox the first putative definitive host. In support of this, preliminary results, obtained by examining guts of some wolves found dead in the same area, have not still revealed the presence of T. serialis tapeworm (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Citterio et al (2021) detected T. serialis eggs in only 0.2% of 2872 red foxes collected from 2012 to 2018 in Northern Italy. Interestingly, Italian wolf ( Canis lupus italicus ), although is a deeply studied species, where hundreds of researches investigate its helminths, has never been diagnosed positive for T. serialis , also considering different regions, ecological setting (anthropic vs not anthropic), and sample size (see for example: Gori et al, 2015 ; Poglayen et al, 2017 ; Macchioni et al, 2021 ), making the red fox the first putative definitive host. In support of this, preliminary results, obtained by examining guts of some wolves found dead in the same area, have not still revealed the presence of T. serialis tapeworm (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to build on previous and current methods to leverage information from scat samples in an intensively monitored wolf population. A few studies have identified helminth infections in wolves across their range using noninvasive methods [ 19 , 20 ], yet samples are often analyzed at the group-level [ 15 , 21 ], or at the individual-level but lack individual-level covariates [ 22 ]; therefore, inference about infections in individual wolves is limited. Additionally, molecular methods are required for identifying parasite taxa with similar egg morphology, such as taeniid cestodes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…granulosus and E . multilocularis , are zoonotic [ 30 , 31 ] and infect and cause disease in livestock [ 22 , 33 , 34 ]. For these reasons, monitoring and preventive medicine development occurs globally [ 35 , 36 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations